Does Urban Security Modulate Transportation Choices and Travel Behavior of Citizens? A National Study in the Dominican Republic - Alonso, Francisco; Useche, Sergio A.; Faus, Mireia; Esteban, Cristina (Frontiers in Sustainable Cities, 2020)
Introduction: Traditionally, the scientific literature on urban and transportation dynamics addresses many topics, but the security-related outcomes of users remain a pending issue, especially in emerging countries and their cities. Nevertheless, recent evidence suggests that, especially in developing countries, security issues may influence people's decision-making in the choice of transport means, daily urban-trip patterns and road behaviors of users. Objective: The purpose of this study was to explore the relationships between the perceived security (in both urban environments and public transport systems) and the daily-travel behavior and trip patterns of the Dominican Republic population. Methods: This cross-sectional study, performed in 2019, analyzed data collected from 1,026 inhabitants from different cities of the Dominican Republic (54% females and 46% males), who completed a survey on security issues, travel behaviors and transportation-related habits. Results: The results of this research suggest that demographic factors, such as age, education, and city/town size, and the safety perceived in the urban environment play a significant role in the choice of transportation modes, as well as in the participants' experience as victims of crime-related incidents (either witnessing or suffering crime episodes on public transport or city streets) during urban trips performed over the last 5 years. Conclusion: Overall, the results of this study suggest that perceived safety, in both urban environments and public transport systems, is a relevant issue affecting the daily transport-related patterns and behavioral choices of the Dominican Republic's population. The results of this research might contribute to the strengthening of transport security planning, considering factors that are not traditionally kept in mind for policymaking in transportation dynamics.